2007
DOI: 10.1007/s00221-007-0917-0
|View full text |Cite
|
Sign up to set email alerts
|

Visual flow influences gait transition speed and preferred walking speed

Abstract: It is typically assumed that basic features of human gait are determined by purely biomechanical factors. In two experiments, we test whether gait transition speed and preferred walking speed are also influenced by visual information about the speed of self-motion. The visual flow during treadmill locomotion was manipulated to be slower than, matched to, or faster than the physical gait speed (visual gains of 0.5, 1.0, 2.0). Higher flow rates elicit significantly lower transition speeds for both the Walk-Run a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(152 citation statements)
references
References 33 publications
12
137
1
2
Order By: Relevance
“…The walk-run and run-walk transition distribution of ostriches exhibited gait-transition hysteresis, and such directional effects on the preferred gait-transition speed cannot be explained by steady-state CoT curves. A similar gait-transition hysteresis has been observed in humans (Thorstensson and Roberthson, 1987;Mohler et al, 2007), and human studies suggest that neural processing and fatigue factors probably influence gait-transition speeds (Mohler et al, 2007;Segers et al, 2007). Thus, while gait transitions of ostriches occur near the energetically optimum speeds (Fig.…”
Section: Gait-transition Speeds and Hysteresissupporting
confidence: 65%
“…The walk-run and run-walk transition distribution of ostriches exhibited gait-transition hysteresis, and such directional effects on the preferred gait-transition speed cannot be explained by steady-state CoT curves. A similar gait-transition hysteresis has been observed in humans (Thorstensson and Roberthson, 1987;Mohler et al, 2007), and human studies suggest that neural processing and fatigue factors probably influence gait-transition speeds (Mohler et al, 2007;Segers et al, 2007). Thus, while gait transitions of ostriches occur near the energetically optimum speeds (Fig.…”
Section: Gait-transition Speeds and Hysteresissupporting
confidence: 65%
“…Previous work has shown that subjects adjust average walking speed after sustained changes in visually presented speed and in a direction opposite the change in perceived speed (De Smet et al 2009;Mohler et al 2007b). However, measures of average speed over a trial mask the amplitude and timing of the fast dynamics that produce this outcome as well as the slow process that eventually cancels it out.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prior knowledge of the association between energy expenditure and walking speed would allow one to immediately predict the energetically optimum adjustments to speed based only on the currently sensed speed. The visual pathways are known to be partially responsible for sensing and making adjustments to walking speed: increasing visual flow rate relative to the actual walking speed elicits significantly slower average preferred speeds, and vice versa (De Smet et al 2009;Mohler et al 2007a;Prokop et al 1997). However, it is still unclear whether vision is used for the rapid gait adjustments that are indicative of indirect prediction, since these studies only used slow visual perturbations that cannot identify the dynamics of the processes involved.…”
mentioning
confidence: 99%
“…Participants were asked to match their power output and pedaling cadence to the average values calculated from their first self-paced time trial. It was necessary to give participants voluntary control of power and cadence in this way so that, consistent with the methods used by Mohler, Thompson, Creem-Regehr, Pick and Warren (2007), the projected video footage was coupled in a multiplicative way to the cyclists' actual power output. The alternative-fixed optic flow video footage-would allow us to precisely fix power and cadence, but, owing to the video being uncoupled to actual cycling behavior creates a far less realistic virtual experience.…”
Section: Cycling Ergometrymentioning
confidence: 99%